Digital Diplomacy in Kenya: A Study on X (Twitter) Analysis and Communication Strategies of A Few Selected Diplomatic Actors - Ong’ong’a, Daniel Oloo (Society & Sustainability, 2023)
The study examined the digital diplomacy practices of three diplomatic actors, namely the US, the UK, and China, in Kenya. To understand how these actors communicate their messages digitally, the study conducted a content analysis of their X tweets, hashtags, hyperlinks, and visuals. Additionally, the study analyzed the tweet impressions section of the posts to gain insight into individual tweet performance, engagement, followers, and following details. These components are crucial in understanding the digital diplomacy practices of the actors. The results showed that the diplomatic actors prioritized following other diplomatic actors, heads of state, online influencers, organizations, projects, and companies of interest, rather than the local Kenyan digital public. The study also found that the preferred topics of the diplomatic actors were tourism, politics, culture, education, and economic development, among others. The reasons for prioritizing certain actors and topics were to monitor activities, protect interests, push foreign policies, expand networks, counter misinformation, and protect image abroad. The findings are presented in the form of a network analysis of tweets to show the communication strategies adopted by the diplomatic actors to influence or exert power over their followers on X.